In-hospital resource utilization, outcome analysis and radiation exposure in children undergoing appendicostomy vs cecostomy tube placement. Issue 5 (October 2020) - Sierralta Born, María Consuelo; Milford, Karen; Rickard, Mandy; Shkumat, Nicholas; Amaral, Joao G.; Koyle, Martin A.; Lorenzo, Armando J.
Summary: Introduction and objectives: Continence enemas for the purpose of bowel management may be delivered via trans-anal retrograde irrigations, and via antegrade conduits including surgical appendicostomy or placement of cecostomy tube (CT). An appreciation of the relative advantages and disadvantages of each antegrade continence enema (ACE) procedure allows clinicians, parents and children to make an informed decision regarding which procedure is most appropriate in individual cases. The objective of this study was to evaluate the differences in in-hospital resource utilization, surgical outcomes and radiation exposure between children undergoing appendicostomy creation and CT placement at our institution. Methods: We conducted a retrospective chart review of children undergoing these procedures at our institution over a 10-year period. All patients 0–18 years of age undergoing either procedure for any indication were included. Data on demographics, length of stay (LOS), radiation exposure events (REE), and surgical outcomes were collected. Results: One hundred fifteen (63 appendicostomy/52 CT) patients were included. Those undergoing CT placement had significantly increased post-procedural LOS, catheter exchanges and REE compared to those undergoing appendicostomy (see Table). Reported rates of bowel control were similar between the two groups, and there was no significant difference in rates of surgical complications, although each group had unique, procedure-specific complications. Discussion and conclusion: In our study, appendicostomy holds a clear advantage over CT in terms of post-procedural LOS, as well as REE. In general, children with CTs require more planned and unplanned device maintenance procedures than those with appendicostomy. These findings aside, the rates of success for bowel control between the two groups are similar, and the incidence of complications does not differ significantly between the two groups. CT remains a safe and effective conduit for delivery of ACEs, and is a particularly good option in patients whose appendix has been lost or used for another conduit. However, patients wishing to avoid repeated procedures and radiation exposure may find the option of appendicostomy more attractive. Summary Table 1 Length of stay, catheter exchanges and radiation exposure metrics. Summary Table 1   Appendicostomy n = 63 (%) Cecostomy n = 52 (%) p -value Post-operative LOS (days)  All patients 2.8 ± 3 5 ± 5 <0.01  Isolated ACE-procedure (n = 38/44) a 2.1 ± 1 4.7 ± 4 <0.0001  Outlier excluded (n = 63/44) a 2.8 ± 3 4.9 ± 4 <0.0001 Duration of antibiotic therapy  Intravenous (all patients) 1.2 ± 1.3 4 ± 13 0.02  Total (all patients) 2.7 ± 5 5 ± 13 0.16  Intravenous(isolated-ACE a ) 0.9 ± 0.9 2 ± 3 0.28  Total (isolated-ACE a ) 1.7 ± 3.5 2.6 ± 4 0.46  Intravenous (outlier excluded a ) 1.2 ± 1.3 2.2 ± 3 0.26  Total (outlier excluded a ) 2.7 ± 5 2.8 ± 4 0.58 Catheter Exchanges  No. catheter exchanges per patient per year of follow-up 0.3 1.1    Total no. patients requiring unplanned catheter exchanges (entire group) 6 (10) 21 (40) <0.01 Radiation Exposure  Total REE (whole group) 71 407    Total number of patients with REE 17 (27) 51 (98) <0.01  Average REE per patient 1.1 c 7.8 <0.01 Radiation exposure metrics b  Total number of REE 50 136    Mean DAP d per event (mGy.cm 2 ) 1003 488 <0.01  Median DAP per event (mGy.cm 2 ) 396 185 <0.01  Mean reference air kerma e per event (mGy) 5.0 3.0 0.0013  Median reference air kerma per event (mGy) 2.8 1.2 0.0013 a Outlier who had 95 days of antibiotics related to cecal detachment and cardiac lesion excluded. b Radiation exposure metrics for REE with complete radiation data (50 events out of 71 events in the appendicostomy group and 136 events out of 407 events in the cecostomy group). c Represents average REE for all appendicostomy patients: average REE in appendicostomy patients with any event at all (17/63) was 4.1. d DAP refers to 'Dose Area Product' and assesses radiation risk using the absorbed radiation dose and the area irradiated during the procedure. e Air kerma is the sum of the initial kinetic energies of all the charged particles liberated by uncharged ionizing radiation (i.e: indirectly ionizing radiation such as photons and neutrons) in a sample of matter. It represents the absorbed dose or gray (Gy). Unlike DAP it is not related to the area radiated, only the dose of radiation.